Soil toposequences, soil erosion, and ancient Maya land use adaptations to pedodiversity in the tropical karstic landscapes of southern Mexico - Sedov, Sergey; Rivera-Uria, M. Yazmin; Ibarra-Arzave, Georgina; García-Ramírez, Pamela; Solleiro-Rebolledo, Elizabeth; Cabadas-Báez, Héctor V.; Valera-Fernández, Daisy; Díaz-Ortega, Jaime; Guillén-Domínguez, Karla A.; Moreno-Roso, Sol de Jesús; Fedick, Scott L.; Leonard, Daniel; et al. (Frontiers in Earth Science, 2023)
The soil mantle of the tropical karst landscapes of southern Mexico was a key resource for ancient Maya agriculture and experienced deep transformation due to long-term human impacts under changing environmental conditions. We conducted a comparative analysis of three compound soil toposequences in mountainous (Sierra de Chiapas/Middle Usumacinta Valley, Budsilhá and Chiniquijá archaeological sites) and platform (NE Yucatán Peninsula, Yalahau region) karst landscapes to reconstruct general tendencies and regional variations in pedodiversity development and soil-human interactions since the Early Preclassic Period.Toposequence characterization is based on macro-and micromorphological observations, accompanied by a suite of laboratory data. Calcareous upland geoforms of all toposequences have similar soil combinations consisting of shallow Rendzina and deep red clayey Terra Rossa types of profiles. We argue that Rendzinas, now dominant in the upland soil cover, in most cases are not a product of incipient pedogenesis on limestone; they developed from the residues of Terra Rossa soils after their advanced erosion. Pedosediments generated by ancient soil erosion are found in the piedmont and depression positions in the mountainous landscapes of Chiapas, as a result of lateral downslope soil removal, and in the subsurface karstic cavities in the platform of NE Yucatán, indicating vertical "soil piping". The soils of 2 the lowland domains show contrasting differences between the toposequences: gleyic clayrich soils and humic alluvial soils prevail in Chiniquihá and Budsilhá whereas hydromorphic carbonate soils are formed in Yalahau karstic depressions. These differences in the lowland soil properties led to divergent ancient Maya landuse strategies: in Chiniquihá and Budsilhá the major agricultural domain was developed in the lowlands; implying largescale artificial drainage. On the contrary in Yalahau mostly upland Rendzinas were cultivated, implying "precision agriculture" and "container gardening".